The influence of symbolic incongruity and religious animosity on negative e-word of mouth with brand hate as a mediating variable on starbucks brand: Pro-Israel and LGBTQIA2+ Issues - Ariqoh, Daffa Asri; Afifah, Nur; Erna Listiana; Barkah, Barkah; Fitriana, Ana (Journal of Management and Digital Business, 2024)
This study examines the factors influencing symbolic incongruity and religious animosity towards negative e-word of mouth through brand hate towards the Starbucks Brand. The research conducted is a causal associative study using a purposive sampling technique. Data were collected through questionnaires from 219 respondents who knew Starbucks in Indonesia. Structural Equation Modeling (SEM) was used to identify the relationship between symbolic incongruity and religious animosity that can affect negative e-word of mouth towards the Starbucks Brand mediated by brand hate. The results of the study indicate that in the five hypothesis tests that have been carried out, it can be said that all relationships between variables, namely symbolic incongruity and religious animosity, have a significant effect and also have a positive effect on negative e-word of mouth with brand hate as a mediating variable. This research can contribute to the role of consumers as parties who make changes because it remembers the importance of understanding consumer perceptions and attitudes, which can influence market dynamics and encourage sustainable economic growth so that a company can manage its strategy well.